Development of an advanced nano-satellite-auto-focus remote sensing camera - Li, Lingpeng (2017)
In recent years, camera is playing on the important role in the satellite research and daily life. So, it is necessary to learn how a camera works. This paper deals with the auto – focusing capabilities found in a camera. This capability helps in aiding our NTU satellites the X-SAT and the VELOX and the upcoming satellites deliver clear and distinct photos in outer space which may translate to the transmission of real – time weather data reports or pictures of our solar system. Three parts of the project will be introduced in this report to provide a detailed understanding. The camera system consists of by three stages which are the image capture component, motor control component and contrast analysis component.